Brief Virtual Observation Revealed the Possibility of Trade in Organophosphate-based Pesticides through E-commerce - Stiawan, Elva; Nurhalimah, Siti; Ananda, Dea Dwi; MS, M. Adrian Rezki Anggara; Tayon, Felix (Jurnal Pengabdian Masyarakat AKA, 2024)
Reactive organophosphates (OPs) could be utilized as deadly pesticides due to their nerve agent properties for several organisms. Although the utilization of these compounds has been strictly regulated, monitoring its trading activities, particularly through e-commerce, could be quite challenging. There is a lack of information on whether the pesticide products containing OPs or slightly featured with similar phosphates groups exist or are un-existed in the online stores in Indonesia. This community service aims to briefly report the possibility of trade in phosphorous-based pesticides through online stores in Indonesia. We demonstrated virtual observation to obtain the list of phosphorous-based pesticides from several e-commerce in Indonesia. We detected 24 pesticides displayed on some popular e-commerce with particular phosphate groups in the active substance, i.e., Acephate, Chlorpyrifos, Dimethoate, Diazinon, Profenofos, and Triazofos. The finding could provide insight for those online stores to establish particular rules to monitor and control trading activities of agrochemicals that could be illegally used or further processed for any activities related to Chemical, Biological, Radiological, and Nuclear and Explosives (CBRN-E) threats.